2016
DOI: 10.5455/tjfmpc.199143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Primary Health Care Services Which Is Provided to Refugees Within a Public Health Center.

Abstract: Background:In recent years, so many people have left their counties because of the war or social, political and economic reasons. This study aims to evaluate the applications of Syrian refugees to a public health center to describe the health care provided to them. Method:The study is intended as a two-part in regard with the mixed design of the study. The first part planned as single-center, descriptive study to be performed with health records of the Syrian asylum seekers and refugees admitted İzmir-Karabagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
1
9
0
7
Order By: Relevance
“…. In the study of Aygün et al, all of the applications are for different people[6]. In our study, a patient presented to the ANTRH for 3.6 times on average.…”
mentioning
confidence: 74%
“…. In the study of Aygün et al, all of the applications are for different people[6]. In our study, a patient presented to the ANTRH for 3.6 times on average.…”
mentioning
confidence: 74%
“…İl Koordinasyon Merkezi tarafından verilen bu tanıtım kartı ile Suriyeli sığınmacılar kamu hastanelerinden ücretsiz sağlık hizmeti alabilmektedirler. 20 Ancak, ilk hastane tedavisinin ardından başka birimlere sevk edilmeleri durumunda (özel birimlere, tahlil vb.) ise ücret ödemeleri gerekmektedir.…”
Section: Discussionunclassified
“…19 Sağ-lık hizmeti sunumunda dil engeli aşılamazsa olumsuz sonuçlar doğurabileceğini ifade eden birçok çalışma mevcuttur. 12,20,21 Bu araştırmada, sığınma-cıların almış oldukları sağlık hizmeti sunumunda, tercüman desteğinden yeteri kadar yararlanamama ve sağlık personelinin ilgisiz/kötü tutumuna bağlı sorunlar yaşadıkları saptanmıştır. Sığınmacılar tarafından ifade edilen bu ilgisizlik durumu, dil engeli nedeni ile iletişim problemi yaşanmış olabileceğini düşündürmektedir.…”
Section: Discussionunclassified
“…In the literature, it has been shown that language barriers negatively affect the quality of 58 health and patient satisfaction, as well as causing unwillingness among the women to benefit from health services (14,23). The language problem is not limited only to the patient's side, but also poses a problem for patient-physician communication for doctors who do not know the language of the patients (24). To solve this problem, it is proposed that brochures should be prepared in the women's mother tongue, interpreting services that can be reached at any time should be provided, and cultural differences should be addressed (17).…”
Section: Maternal Safety Of Syrian Refugees In Southeast Turkeymentioning
confidence: 99%